Etiology of Dyspepsia: Implication for Empiric Therapy. (2002) - Hunt, Richard H; Fallone, Carlo; van Zanten, Sander Veldhuyzen; Sherman, Phil; Flook, Nigel; Smaill, Fiona; Thomson, Alan BR; the Canadian Helicobacter Study Group,
Abstract : Dyspepsia describes a symptom complex thought to arise in the upper gastrointestinal tract and includes, in addition to epigastric pain or discomfort, symptoms such as heartburn, acid regurgitation, excessive burping or belching, a feeling of slow digestion, early satiety, nausea and bloating. Based on the evidence that heartburn cannot be reliably distinguished from other dyspeptic symptoms, the Rome definition appears to be too narrow and restrictive. It is particularly ill suited to the management of uninvestigated dyspepsia at the level of primary care. In patients presenting with uninvestigated dyspepsia, a symptom benefit is associated with a 'test and treat' approach for Helicobacter pylori infection. A substantial proportion of those who do not benefit prove to have esophagitis on endoscopy. In those with functional dyspepsia, the benefits of H pylori eradication, if any, appear to be modest. Hence, a "symptom and treat" acid-suppression trial with proton pump inhibitors, and a 'test and treat' strategy for H pylori are two acceptable empirical therapies for patients with univestigated dyspepsia.